Proceedings of the 15th International Middleware Conference on - Middleware '14 2014
DOI: 10.1145/2663165.2663331
|View full text |Cite
|
Sign up to set email alerts
|

SenSocial

Abstract: Smartphone sensing enables inference of physical context, while online social networks (OSNs) allow mobile applications to harness users' interpersonal relationships. However, OSNs and smartphone sensing remain disconnected, since obstacles, including the synchronization of mobile sensing and OSN monitoring, inefficiency of smartphone sensors, and privacy concerns, stand in the way of merging the information from these two sources.In this paper we present the design, implementation and evaluation of SenSocial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The smartphone is one possibility to collect behavioral data in everyday life [Alvarez-Lozano et al, 2014;Canzian and Musolesi, 2015;LiKamWa et al, 2013;Mehrotra et al, 2014;Saeb et al, 2015;Suhara et al, 2017]. Currently, around 36% of individuals all over the world and 81% of Germans own at least one smartphone, which is used by youths and young adults for an average of 162 min a day [Montag et al, 2015].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The smartphone is one possibility to collect behavioral data in everyday life [Alvarez-Lozano et al, 2014;Canzian and Musolesi, 2015;LiKamWa et al, 2013;Mehrotra et al, 2014;Saeb et al, 2015;Suhara et al, 2017]. Currently, around 36% of individuals all over the world and 81% of Germans own at least one smartphone, which is used by youths and young adults for an average of 162 min a day [Montag et al, 2015].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Our analysis has shown that most studied proposals have addressed energy efficiency issues, while only some of them have introduced mechanisms to mitigate security and privacy concerns. In fact, we find that only a few solutions [38,113,2,83,134] actually account for both privacy and energy efficiency issues. We now proceed to discuss these prominent solutions in more detail.…”
Section: Privacy and Energy Issuesmentioning
confidence: 95%
“…Figure 2.2 shows the number of crowdsensing-related proposal search on different impact journal and conference, and that mobile crowdsensing applications have experienced a significant increase in the last five years. Specifically, researchers have focused their efforts on various areas including environment monitoring [105,108,113,145], transportation and urban sensing [6,26,67,75,117], healthcare [54,78,100,128,155], social issues [21,49,83,92,130], and others [38,97,103,135,146]. The different crowdsensing proposals available are characterized by having different designs, and involve different architectural levels.…”
Section: The Crowdsensing Conceptmentioning
confidence: 99%
See 2 more Smart Citations